Metaphysics and the good themes from the philosophy of Robert Merrihew Adams - Newlands, Samuel; Jorgensen, Larry M. (Oxford : Oxford University Press, 2009)
A collection of original essays by leading philosophers dedicated to exploring many of the facets of Robert M. Adams's thought, a philosophical outlook that combines Christian theism neo-Platonism, moral realism, metaphysical idealism, and a commitment to both historical sensitivity and rigorous analytic engagement.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Adams, Robert Merrihew; Philosophy, American -- 20th century; Philosophical theology; Metaphysics